A primer on the drivers of labor income share - Saumik Paul; Yoko Oishi (Asian Development Bank Institute (ADBI), 2018)
Despite its long pedigree, studies on the role of the substitution elasticity between capital and labor mostly assume a homogeneous labor market. This paper extends this literature by considering a heterogeneous labor market with capital-skill complementarity. Technological advancement, global integration, regulation of labor market and structural transformation also play important roles in the distribution of income. However, the process of structural transformation, technological advancement, and the promotion of skill deepening varies significantly across developing economies. It is imperative that we identify the factors behind these diverse trends to design policies for a more equitable distribution of income in the developing economies. To this extent, we suggest a deeper analysis of the role of firm restructuring, skilled emigration, and premature deindustrialization, among others.
Keywords: E24; E22; E25; 330; labor income share; substitution elasticity; drivers of labor income share